E-PAYMENT INNOVATION IN IMPROVING BANK INDONESIA'S FINANCIAL PERFORMANCE - Rahyuni Rahayu; Wana Mariska; Muhammad Fauzan Garantjang (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Business competition in the financial services industry keeps the banks constantly innovating in services and products. One of the innovations made by the banking industry is e-payment.This study aims to determine the effect of e-payment on financial performance with moderated bank size. The population in this study is banking companies listed on the Indonesian Stock Exchange (IDX) in 2014-2016 as many as 43 banks. Sample selection method used is purposive sampling, so that obtained the number of samples of 10 banks. The data obtained were analyzed using Moderated Regression Analysis (MRA). The results of this study indicate that e-payment has a significant positive effect on financial performance and bank size strengthen the relationship between e-payment to financial performance. The results indicate that innovation in adopting e-payment can improve bank financial performance. The banks need to pay attention to innovation in financial services as a competitive strategy to improve financial performance.